Optimised GMP-compliant production of [18F]DPA-714 on the Trasis AllinOne module - Klaudia A. Cybulska; Vera Bloemers; Lars R. Perk; Peter Laverman (SpringerOpen, 2021)
Abstract Background The translocator protein 18 kDa is recognised as an important biomarker for neuroinflammation due to its soaring expression in microglia. This process is common for various neurological disorders. DPA-714 is a potent TSPO-specific ligand which found its use in Positron Emission Tomography following substitution of fluorine-19 with fluorine-18, a positron-emitting radionuclide. [18F]DPA-714 enables visualisation of inflammatory processes in vivo non-invasively. Radiolabelling of this tracer is well described in literature, including validation for clinical use. Here, we report significant enhancements to the process which resulted in the design of a fully GMP-compliant robust synthesis of [18F]DPA-714 on a popular cassette-based system, Trasis AllinOne, boosting reliability, throughput, and introducing a significant degree of simplicity. Results [18F]DPA-714 was synthesised using the classic nucleophilic aliphatic substitution on a good leaving group, tosylate, with [18F]fluoride using tetraethylammonium bicarbonate in acetonitrile at 100∘C. The process was fully automated on a Trasis AllinOne synthesiser using an in-house designed cassette and sequence. With a relatively small precursor load of 4 mg, [18F]DPA-714 was obtained with consistently high radiochemical yields of 55-71% (n=6) and molar activities of 117-350 GBq/µmol at end of synthesis. With a single production batch, starting with 31-42 GBq of [18F]fluoride, between 13-20 GBq of the tracer can be produced, enabling multi-centre studies. Conclusion To the best of our knowledge, the process presented herein is the most efficient [18F]DPA-714 synthesis, with advantageous GMP compliance. The use of a Trasis AllinOne synthesiser increases reliability and allows rapid training of production staff.